A face oculta do documento: tradição e inovação no limiar da Ciência da informação - Rabello, Rodrigo [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Among the countless research possibilities in the field of Information Science (IS), the historical-conceptual approach is relevant when we observe intents of systematization and theoretical deepening of this analytical sphere with markedly epistemological concerns. Taking into consideration this research universe, it was observed that the concept document has a privileged position in the “protective belt” of the “scientific research program” of Imre Lakatos adapted to IS by Miguel Rendón Rojas. However, it was seen repeatedly that the document was approached inaccurately in the field of IS, mainly when conceptual aspects related one moment by tradition, and the next by innovation were not counterbalanced. Bearing in mind the objective of the study and the identified problematics, we resorted to the disciplines of History, Diplomatics and Documentation as they were relevant to a historical and conceptual approach, precisely for having studied the document prior to IS. The research of these disciplines was justified by the hypotheses that they have influenced and/or contributed to the meaning of document while a category in the theoretical universe of IS. Based on this conjecture, the following objectives arose: a) to carry out a historical and conceptual study to learn to what extent the analyzed disciplines have contributed for the meaning of document in IS; and b) to understand the nature and the range of the concept in IS when seen under a social perspective that contemplated the dynamic relationship between tradition and innovation in its theoretical framework. Therefore, tradition and innovation are considered as antithetical categories of analysis inspired on those that make up Historik by Reinhart Koselleck and that represent respectively “reality rates” and “perspectives of the future” of the concept document, if seen, above all, from the point of view... (Completo abstract click electronic access below)

Dentre as inúmeras possibilidades investigativas no campo da Ciência da Informação (CI), a abordagem histórico-conceitual se faz relevante num momento em que se observam intentos de sistematização e de aprofundamento teórico desta esfera analítica, com preocupações marcadamente epistemológicas. Considerando esse universo investigativo, observou-se que o conceito documento apresenta uma posição privilegiada na “cintura protetora” do “programa de investigação científica” de Imre Lakatos, adaptado à CI por Miguel Rendón Rojas. Todavia, identificou-se que, muitas vezes, o documento fora abordado no campo da CI de forma imprecisa, principalmente, quando não foram sopesados aspectos conceituais relacionados ora pela tradição, ora pela inovação. Tendo em vista o objeto de estudo e a problemática identificada, recorreu-se às disciplinas História, Diplomática e Documentação por serem importantes para uma abordagem histórico-conceitual, justamente por reunirem esforços anteriores à CI para o estudo do documento. A investigação dessas disciplinas se justificou a partir da hipótese de que elas influenciaram e/ou contribuíram para a acepção de documento enquanto uma categoria no universo teórico da CI. Dessa conjectura, emergiram os seguintes objetivos: a) realizar um estudo histórico-conceitual para apreender em que medida as disciplinas analisadas contribuíram para a acepção de documento na CI; e b) compreender a natureza e a abrangência do conceito na CI quando pensado a partir de uma perspectiva social que contemplasse a relação dinâmica entre tradição e inovação no seu quadro teórico. Para tanto, configuram-se tradição e inovação enquanto categorias antitéticas de análise inspiradas naquelas que compõem a Historik de Reinhart Koselleck e que representam, respectivamente, “índices de realidades” e “perspectivas de futuro”...
Keywords: Ciência da informação; Epistemologia; Documento - Conceito; Documen; History of concepts; History; Diplomatics; Documentation; Information Science